THE ROLE OF CARE RECIPIENT NATIVITY STATUS IN THEIR CAREGIVERS' QUALITY OF LIFE. (11th November 2018) - Moon, H; Sears, J; Rote, S; Haley, W E
Abstract: While much attention has been given to caregiving in the general population, less research has been conducted on the potentially unique experiences and outcomes of caregivers (CGs) of foreign-born older adults. Guided by Pearlin and colleagues' (1990) Stress Process Model (SPM), the current study examined the interaction effects of care recipient (CR) nativity status on the associations between race/ethnicity and the psychological well-being/self-rated health of older adult CGs using nationally representative data, the National Health and Aging Trends Study (NHATS, N=1, 293) and the National Study of Caregiving (NSOC, N=1, 293). We found that race/ethnicity and nativity combine in complex ways. For example, CGs to Black immigrants reported better psychological well-being and self-rated health compared to CGs of Black US born CRs. CGs to Latino immigrants reported better psychological well-being but worse self-rated health than CGs of Latino US-born CRs. Further research is needed to investigate variations in caregiver stress processes.